Reply to Landwehr, K.R.; Larcombe, A.N. Comment on “Karthikeyan et al. Concordance between In Vitro and In Vivo Relative Toxic Potencies of Diesel Exhaust Particles from Different Biodiesel Blends. Toxics 2024, 12, 290” - Subramanian Karthikeyan; Dalibor Breznan; Errol M. Thomson; Erica Blais; Premkumari Kumarathasan (Toxics)
This reply aims to address the comments made by Landwehr and Larcombe [...]